2015
DOI: 10.3109/00365521.2015.1121514
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised study of dense Infinity cytological brush versus regularly used brush in pancreaticobiliary malignancy

Abstract: With the standardised technique, the sensitivity of brush cytology is fairly good. The dense Infinity® brush does not show any advantage regarding sensitivity compared with the conventional cytology brush.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
(6 reference statements)
2
11
1
Order By: Relevance
“…In previous analyses, the risk of PEP in our unit has been 2.0-3.3%. 29,30 The sample size determination for this study was carried out as follows: power = 0.8; α = 0.05; and to lower the risk from 3.0 to 1.0% needs a sample of 1528 patients (764 + 764). We included 2000 patients in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous analyses, the risk of PEP in our unit has been 2.0-3.3%. 29,30 The sample size determination for this study was carried out as follows: power = 0.8; α = 0.05; and to lower the risk from 3.0 to 1.0% needs a sample of 1528 patients (764 + 764). We included 2000 patients in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The annual volume in our unit is 1200 ERCP procedures, and the overall risk of PEP has varied between 2.0 and 3.3%. 29,30…”
Section: Introductionmentioning
confidence: 99%
“…A similar prospective study of 60 patients with biliary strictures suspicious for malignancy randomized patients to either the Infinity brush ( n = 30) or a standard cytology brush ( n = 30) . Patients were followed for a median of 11 months and all of the patients were later diagnosed with malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…A similar prospective study of 60 patients with biliary strictures suspicious for malignancy randomized patients to either the Infinity brush (n 5 30) or a standard cytology brush (n 5 30). 9 Patients were followed for a median of 11 months and all of the patients were later diagnosed with malignancy. The biliary brush cytology samples were graded by experienced pathologists using three categories: (1) Furthermore, the diagnostic accuracy of the standard brush was significantly better than the Infinity brush.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the Infinity ERCP sampling device increases diagnostic accuracy, likely due to improved cellular yield 17 . However, a 2015 randomized controlled trial also compared the Infinity ERCP sampling device against a traditional brush in the setting of a suspected malignant biliary stricture, and found a higher cancer detection rate and sample quality with the traditional brush 18 .…”
Section: Introductionmentioning
confidence: 99%